2011
DOI: 10.1111/j.1743-6109.2010.02190.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Monoamine Pharmacological Agents in the Treatment of Sexual Dysfunction: Evidence in the Literature

Abstract: Introduction The monoamine neurotransmitters serotonin, dopamine, and norepinephrine play an important role in many medical and psychological conditions, including sexual responsiveness and behavior. Pharmacological agents that modulate monoamines may help alleviate sexual dysfunction. Aims To provide an overview of pharmacological agents that modulate monoamines and their use in the treatment of sexual dysfunction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…These side effects are present in 30% to 73% of users . In line with this, animal sexual behavior studies have shown that acute or chronic treatment with SSRIs inhibits sexual behavior in males and females . The inhibitory effects of fluoxetine (FLX) and other SSRIs on female sexual behavior may be veiled by their disruptive actions on the regularity of the estrous cycle .…”
Section: Introductionmentioning
confidence: 89%
“…These side effects are present in 30% to 73% of users . In line with this, animal sexual behavior studies have shown that acute or chronic treatment with SSRIs inhibits sexual behavior in males and females . The inhibitory effects of fluoxetine (FLX) and other SSRIs on female sexual behavior may be veiled by their disruptive actions on the regularity of the estrous cycle .…”
Section: Introductionmentioning
confidence: 89%
“…In one open trial where 13 patients reported sexual dysfunction after they began with antidepressant treatment, sexual function, measured by use of the Arizona Sexual Experience Scale and Clinical Global Impression of Improvement scales, showed a significant effect on both scales 3 weeks after initiation of treatment with ropinirole . The doses of ropinirole (3–4 mg/day) in the latter study were markedly lower than the doses (20–25 mg/day) described to cause hypersexuality and sexual urges in patients with Parkinson's disease . Therefore, the potential for treating ED of mixed origin by selective agonists for dopamine D 2 or D 3 receptors remains to be explored, although the effects on potentially severe side effects as behaviour and blood pressure should be taken into account.…”
Section: Pharmacological Modulation Of the Dopaminergic Pathways To Imentioning
confidence: 91%
“…Reward structures are clearly implicated in sexual anticipation through receipt [73]. Dopamine agonists increase sex behaviors [74] and enhance sexual response [75]. …”
Section: Methodsmentioning
confidence: 99%